2023
DOI: 10.17718/tojde.1088388
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Challenges and Opportunities for Improvements of Distance Learning in Teacher Education: Kosovo’s Experience

Abstract: This study aims to investigate the pre-service teachers’ experiences with online teaching, but also to uncover the challenges and opportunities for improving the distance education in the future. A qualitative research approach using phenomenology is adapted for the study. The participants were 18 pre-service teachers studying at the different programs of the University of Prishtina’s Faculty of Education. The interviews were conducted online. The transcripts of interviews were analyzed using the interpretativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Other challenges were related to the quality of online teaching and overall learning outcomes and satisfaction with online education. A qualitative study by Nikoçeviq-Kurti (2023) found that pre-service teachers encountered challenges including technological skills, unrealistic assessments, and students being overloaded with assignments not counted in final assessments. Some participants reported that the practical portion of online classes was entirely absent, despite its importance for them, while some educators lacked motivation when teaching online.…”
Section: Challenges Of Online Learning For Pre-service Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Other challenges were related to the quality of online teaching and overall learning outcomes and satisfaction with online education. A qualitative study by Nikoçeviq-Kurti (2023) found that pre-service teachers encountered challenges including technological skills, unrealistic assessments, and students being overloaded with assignments not counted in final assessments. Some participants reported that the practical portion of online classes was entirely absent, despite its importance for them, while some educators lacked motivation when teaching online.…”
Section: Challenges Of Online Learning For Pre-service Teachersmentioning
confidence: 99%
“…We found no literature consistent with our finding of no significant association of effective teaching and learning in online education with pre-service teachers' age, marital status, or employment status. Nevertheless, some studies reveal factors influencing online teaching effectiveness generally, such as effective communication (Liu et al, 2022), self-confidence and technology use (Teoh et al, 2023), challenges (Nikoçeviq-Kurti, 2023), and support (Pourdavood and Song, 2021). Although demographic characteristics may not have a substantial impact on the efficiency of online teaching and learning for pre-service teachers in this study, research conducted in other locations on in-service teachers, such as in the Philippines (Sacramento et al, 2021), indicates that the factors impacting the success of online education can fluctuate depending on the specific setting.…”
Section: Research Questionmentioning
confidence: 99%